Analisis Pengalaman Pengguna pada Situs Distribusi Digital menggunakan Metode Usability Testing dan User Experience Questionnaire (Studi pada store.steampowered.com dan gog.com) - Munggarhanna Aschi Putra Jayana; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The development of information technology has grown rapidly and has influenced human life. E-commerce makes business competition move to network level, products in the form of licenses become a big prospect in business, and notice this as an opportunity known as digital distribution, two digital distribution sites which have similar business processes with knownly quite high visitors namely, store.steampowered.com and gog.com. Aim of the study is to compare user experience on the websites which have same characteristics and business processes in terms of usability.This study is using 2 testing methods, first is usability testing in the form of a scenario test that contains 6 (six) tasks with 4 (four) parameters which are tasks success rate, time per completed task, number of clicks during task completion, and error during task performance and user experience questionnaire which has 6 (six) scales namely: attractiveness, efficiency, perspicuity, dependability, stimulation, and novelty Respondents and test participants have different backgrounds with the range of the age are between 18-35 years old who have never used the two websites. Then study was strenghtened by focus discussion group (FGD) method to seek deeper meaning about user perspective and problems found. From the results of the analysis and comparison based on the methodolgy, Steam's test result is superior than gog's based on 4 test parameters conducted, the respondents from UEQ are giving good impressions which achieved positive (good) mean level on every UEQ scale. FGD and feedback test result from scenario task used for seeking detailed preception and user problems. From both tests performed it can be concluded that the store.steampowered.com site is better than gog.com.